Air Conditioner Condensate and Mineral Water as Alternative Solvents for Potato Dextrose Agar: Comparative Growth of Trichophyton rubrum - Martha Atik Martsiningsih; Yusmiarti Yusmiarti; Anik Nuryati; Siti Nur Azizah; Menik Kasiyati; Budi Setiawan (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2026)
Trichophyton rubrum is the predominant cause of dermatophytosis worldwide, particularly in tropical countries such as Indonesia. Potato Dextrose Agar (PDA) is a standard medium for fungal culture, conventionally prepared with distilled water; however, its limited availability and high cost in resource-constrained laboratories necessitate alternative solvents. This study aimed to evaluate the growth of T. rubrum on PDA prepared with distilled water, air conditioner (AC) condensate, and bottled mineral water by comparing colony diameter and morphology. A quasi-experimental study with a post-test-only non-equivalent control group design was conducted. PDA was prepared using the three solvents, inoculated by the single-dot method, and incubated at a fixed temperature of 28°C for 7 days. Colony diameter and macroscopic and microscopic morphology were assessed. Statistical analyses included the Shapiro–Wilk test, One-Way ANOVA, and Independent Sample T-test (p < 0.05). All media supported typical T. rubrum growth. Colony diameters obtained using AC condensate were not significantly different from those obtained using distilled water, whereas mineral water resulted in significantly smaller colonies. These findings indicate that AC condensate can serve as an effective and economical substitute for distilled water in PDA preparation, while the use of mineral water should be limited due to variability in composition and lack of standardization.